The Children – Sit Less, Move More (C-SLAMM) pilot intervention: Feasibility and acceptability of a multi-component school and home-based intervention to promote physical activity - Sarah Nally; Angela Carlin; Alison M. Gallagher; Jason J. Wilson; Ian M. Lahart; Jo Salmon; Marie H. Murphy (PLoS ONE, 2025)
Background A high proportion of primary school children in Northern Ireland (NI) are insufficiently active. In response, an intervention adapted from the TransformUs programme was established to promote physical activity (PA) and reduce sedentary behaviour (SB). This study aimed to assess the feasibility of recruitment and retention, data collection procedures, intervention acceptability and explore preliminary effectiveness on children’s PA and SB levels. Methods The Children – Sit Less, Move More (C-SLAMM ) intervention integrated behavioural, pedagogical, and environmental strategies across classroom, school, and home settings. Eight primary schools were recruited and randomly assigned (1:1) to either the intervention or control. Feasibility measures included school and participant recruitment, retention and completion rates. Acceptability was assessed using weekly diary logbooks, fidelity checklists and qualitative methods (write and draw activity, focus groups, interviews). Children (aged 7–9 years) wore activPAL accelerometers continuously for 7 days at baseline and post-intervention (Week 8) to measure time spent sitting, standing, and stepping. Results A total of 194 consent forms were distributed. Of the 162 children who consented (84% response rate), 76 (46.9%) met the valid wear-time criteria at both baseline and follow-up. Intervention delivery varied across schools, impacting fidelity. Qualitative analysis revealed four themes: (1) engagement, (2) positive aspects of C-SLAMM intervention, (3) barriers to intervention delivery, and (4) recommendations for improvement. Children and teachers generally found the intervention acceptable, though barriers included limited parental support, inadequate classroom space and time constraints. There were no significant differences in sitting time (β = −6.5 minutes/day; 95%CI: −36.4, 23.4), standing or stepping time between groups. Nevertheless, the intervention was seen as enhancing classroom experiences for both children and teachers. Conclusions The C-SLAMM intervention was well-received and shows promise as an acceptable approach to reduce sitting time and promote PA. Further refinement of data collection methods is needed before progressing to a pilot trial. Trial registration ClinicalTrials.gov, NCT05854355 (submitted on the 30 th of March 2023).